2023
DOI: 10.3390/ani13111811
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and Androstenedione Are Important Follicular Fluid Factors Regulating Porcine Oocyte Maturation Quality

Abstract: Oocytes matured in vitro are useful for assisted human and farm animal reproduction. However, the quality of in vitro matured oocytes is usually lower than that of in vivo matured oocytes, possibly due to the absence of some important signal regulators in vitro. In this study, untargeted metabolomics was used to detect the changes in the metabolites in the follicular fluid (FF) during in vivo pig oocyte maturation and in the culture medium during in vitro maturation. Our results showed that the total metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Because in the pig species, the processes of meiotic resumption as well as oocyte transition to MII are steroid-dependent (Zavareh, et al, 2013), decrease in P4 concentrations could affect IVM. It has been previously reported that adding RU486, a P4 inhibitor, to porcine oocyte maturation medium, decreases IVM and embryo development (Yuan, et al, 2016), while 100 µM of P4 added to porcine COCs culture medium increases IVM and embryo development (Zhao, et al, 2023). Therefore, the decrease in P4 concentrations in oocytes exposed to 650 and 780 µM MePB could explain one of the mechanisms by which IVM decreases.…”
Section: Evaluation Of P4 Synthesis In Culture Mediummentioning
confidence: 95%
See 1 more Smart Citation
“…Because in the pig species, the processes of meiotic resumption as well as oocyte transition to MII are steroid-dependent (Zavareh, et al, 2013), decrease in P4 concentrations could affect IVM. It has been previously reported that adding RU486, a P4 inhibitor, to porcine oocyte maturation medium, decreases IVM and embryo development (Yuan, et al, 2016), while 100 µM of P4 added to porcine COCs culture medium increases IVM and embryo development (Zhao, et al, 2023). Therefore, the decrease in P4 concentrations in oocytes exposed to 650 and 780 µM MePB could explain one of the mechanisms by which IVM decreases.…”
Section: Evaluation Of P4 Synthesis In Culture Mediummentioning
confidence: 95%
“…It has been previously reported that the concentration of P4 present in the follicular uid is positively related to the development potential of oocytes, making it an indicator of the quality of IVM (Zhao, et al, 2023). Because in the pig species, the processes of meiotic resumption as well as oocyte transition to MII are steroid-dependent (Zavareh, et al, 2013), decrease in P4 concentrations could affect IVM.…”
Section: Evaluation Of P4 Synthesis In Culture Mediummentioning
confidence: 99%